2022
DOI: 10.1021/acsaem.2c01331
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Photogenerated Carrier Transport by Integration of Sb2O3 with Fe2O3 for Improved Photoelectrochemical Water Oxidation

Abstract: Optimization of photogenerated carrier transport by heterojunction engineering has been realized as an effective strategy to improve the electrode performance in photoelectrochemical (PEC) systems. We report for the first time a type II heterostructure consisting of Sb2O3 and Fe2O3 for significantly enhanced PEC water oxidation. The as-fabricated photoanode exhibits prominent performance with a photocurrent density as high as 1.31 mA cm–2 at 1.23 V (vs. reversible hydrogen electrode), 14.5 times that of bare F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…The donor density of the HfO 2 /α - Fe 2 O 3 film is about 1.95 × 10 20 cm −3 , which is almost 2 times higher than that of α - Fe 2 O 3 film (about 1.15 × 10 20 cm −3 ). This finding demonstrated that the heterojunction successfully increased the PEC performance by increasing conductivity, facilitating the fast transfer of photogenerated carriers, and increasing the degree of semiconductor energy band bending [ 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…The donor density of the HfO 2 /α - Fe 2 O 3 film is about 1.95 × 10 20 cm −3 , which is almost 2 times higher than that of α - Fe 2 O 3 film (about 1.15 × 10 20 cm −3 ). This finding demonstrated that the heterojunction successfully increased the PEC performance by increasing conductivity, facilitating the fast transfer of photogenerated carriers, and increasing the degree of semiconductor energy band bending [ 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…High-efficiency solar-to-hydrogen production has attracted promising attention due to its clean and carbon-neutral characteristics, which provides a pathway to overcoming the global energy crisis and environmental issues. , Thereinto, photoelectrochemical (PEC) water splitting is convincing as an intriguing avenue for hydrogen production from abundant solar energy and water with high purity. However, the sluggish kinetics of the water oxidation process, derived from the complicated four-electron transfer pathway, seriously impede the development in practical applications. TiO 2 is one of the most promising semiconductor photoanodes due to its favorable valence-band position, high activity, and robust stability. Nevertheless, bare TiO 2 undergoes intrinsic drawbacks such as a large bandgap, high recombination rate, and slow kinetics of oxygen evolution. , Designing and engineering excellent photoanodes, simultaneously possessing high charge carrier separation, wide absorption range, and water oxidation kinetics, still face great challenges. , …”
Section: Introductionmentioning
confidence: 99%
“…12,13 Designing and engineering excellent photoanodes, simultaneously possessing high charge carrier separation, wide absorption range, and water oxidation kinetics, still face great challenges. 14,15 To improve the PEC performance, several approaches have been adopted and developed, such as heterostructure construction, elemental doping, cocatalyst modification, or surface state passivation. 16−18 Heterostructure construction by coupling semiconductors with small bandgaps is a promising pathway to improve light utilization and electron−hole separation.…”
Section: Introductionmentioning
confidence: 99%